The Obsidians (Oliver Blue and the School for Seers-Book Three) - Morgan, Rice (Lukeman Literary, 2019)
"A powerful opener to a series [that] will produce a combination of feisty protagonists and challenging circumstances to thoroughly involve not just young adults, but adult fantasy fans who seek epic stories fueled by powerful friendships and adversaries." --Midwest Book Review (Diane Donovan) (re A Throne for Sisters) "Morgan Rice's imagination is limitless!" --Books and Movie Reviews (re A Throne for Sisters) From #1 Bestselling fantasy author Morgan Rice comes a new series for middle grade readers (and beyond)! Fans of Harry Potter and Percy Jackson-look no further! In THE OBSIDIANS: OLIVER BLUE AND THE SCHOOL FOR SEERS (BOOK THREE), 11 year old Oliver Blue once again finds himself in the race of his life. His beloved friend Esther is dying of time-travel sickness, and the only chance of saving her is to risk his life and travel back in time once more. This time, it is to the Italy of the 1400s, to visit two very important people: Leonardo Da Vinci, and his rival, Michelangelo. Only Leonardo's inventions hold the answer; and only Michelangelo's paintings hold the key. The Obsidians, though, are bent on revenge, and Chris is determined to not stop until his little brother is done. An uplifting fantasy, THE OBSIDIANS is book #3 in a riveting new series filled with magic, love, humor, heartbreak, tragedy, destiny, and a string of shocking surprises. It will make you fall in love with OLIVER BLUE, and keep you turning pages late into the night. Book #4 in the series will be available soon! "The beginnings of something remarkable are there." --San Francisco Book Review (re A Quest of Heroes)
Keywords: Dobrodružství, napětí, fantasy